Physical Properties of Petroleum Products Marketed in Congo - Ulrich Berry; Smäel Magloire Elombo Motoula; Westinevy Benarez Ndzessou (Mikailalsys Journal of Advanced Engineering International, 2026)
The use of fuels and combustibles in internal combustion engines requires strict quality standards to ensure operational efficiency and to limit the environmental impact of emissions. This study focuses on the characterization of the physical properties of petroleum products marketed in Congo, with particular attention to parameters that are critical for proper engine functioning and environmental performance. To achieve this objective, a series of laboratory analyses was conducted on petroleum product samples to determine mass density, specific gravity, color, pH, and viscosity. These measurements were obtained using a controlled experimental setup that included a precision balance, test tube, stopwatch, and an aluminum-ball arrangement for viscosity determination. The characterization carried out provides a coherent description of the physical quality of the petroleum products examined and illustrates how essential fuel properties can be systematically monitored through relatively simple but rigorous testing procedures. The study concludes that careful control of these physical parameters is fundamental to ensuring that petroleum products meet the standards required for safe, efficient engine operation and for reducing the potential contribution of inadequate fuel quality to environmental pollution, thereby underscoring the importance of strengthening quality control practices in the fuel supply chain.